REGISTRY OF ACUTE CEREBRAL CIRCULATORY DISORDERS LIS-2: NEW DATA ON LONG-TERM FOLLOW-UP - S. Yu. Martsevich; N. P. Kutishenko; A. V. Zagrebelnyy; Yu. V. Lukina; М. L. Ginzburg; A. V. Fokina; E. V. Daniels; A. D. Deev (Столичная издательская компания, 2018)
Aim. To assess long-term outcomes in patients after acute stroke within LIS-2 registry.Material and methods. 960 patients hospitalized in 2009-2011 due to acute stroke in one of the district hospitals of Lyubertsy town were included into analysis. The first assessment of the life status was carried out in 2012-2013 through 2.8 [2.1; 3.5] years after discharge, and a reassessment was in 2017 through 7-8 years after discharge, median follow-up 6.1 [6.9; 7.7] years. The primary endpoint was total mortality. Survival was assessed using the Kaplan-Meier curves.Results. Only 300 patients were alive by the end of the follow-up, 543 patients died, and life status of 117 patients were unknown. Kaplan-Mayer curves showed that mortality was the highest during the first year after stroke, and then it stabilized and remained unchanged till the end of the followup. Less than a third of patients were alive after 8 years of follow-up. The identification of causes of death was difficult in a significant number of cases (in 52% of cases the cause was unknown). Acute stroke and other cerebrovascular diseases, as causes of death, were found in 15% of deaths, other cardiovascular diseases - in 18%, oncological diseases - in 7%, injuries - in 4%. Such causes of death as acute myocardial infarction, pulmonary disease or pulmonary embolism accounted for only 2% in the structure of deaths. A trend towards decrease in the proportion of recurrent stroke as the cause of death was observed as the follow-up period increases.Conclusion. Mortality rate of patients after acute stroke remains stably high throughout the follow-up period: after 8 years less than a third of patients were alive. Death from acute stroke and cardiovascular diseases prevailed among the main causes of death at a distant stage of observation. It is necessary to analyze the factors determining the long-term outcomes at different periods after the stroke.